In pursuit of humane and sustainable housing patterns on the island of Cyprus - Oktay, Derya; Pontikis, Kyriakos (Taylor & Francis Inc, 2008)
The newly developed urban environment often shows extensive neglect of local values and a lack of design promoting environmental quality in our cities and towns within the 'economic' concept of a city. Most housing environments, particularly those produced on the basis of mass production systems, are missing vital aspects of sustainability and lack environmental and humane qualities, both at urban and architectural levels. It is essential to focus on the requirements of sustainable development, both as a philosophy of planning and design and during the process of making and managing our environments. Current urban and architectural development practices in Cyprus cannot be considered sustainable. However, traditional settlements on Cyprus, such as the vernacular patterns, are excellent examples to learn from as they represent a long-established culture and good use of local values and resources, matched with local skills meeting people's needs. This paper first focuses on what sustainability means in terms of housing environments by highlighting the qualities of traditional housing patterns in Cypriot settlements. Second, it provides a critical evaluation of newly developed housing patterns on the island in terms of the environment and traditions. Finally, it proposes principles of sustainable planning and design whose main aim is to create buildings that are sensitive to people and the environment and are culturally specific.
Keywords: housing; old housing patterns; new housing patterns; sustainability; Cyprus